Micro-scale measurement and FEM modelling of residual stresses in AA6082-T6 Al alloy generated by wire EDM cutting - Salvati, E; Korsunsky, A (Elsevier, 2019)
Wire EDM is well-known as a technique for sectioning metallic samples that causes minimal disturbance in terms of residual stress introduction and modification at the macro-scale. Indeed, at the millimetre scale, EDM-induced residual stress can usually be neglected. However, when the dimensions of the machined product are reduced to less than a few millimetres, the structural modification of the EDM affected layer may play a significant role in altering its structural integrity through microstructural changes and induced residual stresses. The surface finish and mechanical properties of the modified surface layer are of great importance for the correct assessment of the in-service life of mechanical components and assemblies. In this study, the EDM-affected layer generated after the primary cut, and also after a subsequent trim cut are analysed. The key advance reported in the present study is the micro- to nano-scale residual stress evaluation and modelling using the FIB-DIC method, supported and validated against non-linear thermo-mechanical FEM analysis of the cutting process. Modelling of such a machining process has a relevant implications in the optimisation of the process parameters. A thin compressive residual stress layer was found at the surface of the sample which was attributed to the Cu and Zn diffusion within the parent material, giving rise to phase transformation. Scanning Electron Microscopy with Focused Ion Beam milling were employed for the exploration of the surface and through-thickness morphology. EDS and EBSD techniques were used to interrogate the material microstructure in terms of elemental concentration and grain orientation. The implications of these findings are discussed.